PENDAMPINGAN DIGITALISASI KEWIRAUSAHAAN UMKM TERDAMPAK COVID-19 - Dwanita Widodo, Zandra; Eni Maryanti, Istinganah; Harsono, Mugi; Darmaningrum, Kurniawati; Adiyani, Rini; Wijiastuti, Sri (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
The second-year Covid-19 pandemic becomes an emergency pandemic in Indonesia. Economic movement begins to creep gradually to get out of recession. Covid-19 exerts a great effect on MSMEs around us. We, as the academicians implementing tridharma (three pillars) of university, are responsible for realizing the expectation and the ideals of our brothers/sisters who establish MSMEs and fighting for surviving amid Covid-19, and make this the background of current community service. This community service activity was conducted in Jaten Village area, Jaten Sub District, Karanganyar Regency, Central Java Province, with the MSME actors being the target of program. This activity was conducted for one day to maximize the facilitation of entrepreneurship digitalization as the attempt to boost the economic growth rate in MSMEs affected by Covid-19 through mojo and siapik application. This activity implementation was done used training and facilitation method. These two methods were implemented by giving information, role play, FGD, simulation, practice, and reflection. The output of activity is to improve the sale performance through digitalization, to give added value to entrepreneurial knowledge thereby helping MSME actors in vending their product and service. The enthusiasm of MSME actors to keep stepping forward vigorously to pass through Covid-19 gives them positive energy to fight for recovering their family economy. The activity ran well and effectively.